PERANAN LEMBAGA PEMASYARAKATAN DALAM MENJAGA KEAMANAN TERHADAP TERJADINYA PELARIAN NARAPIDANA (STUDI KASUS LEMBAGA PEMASYARAKATAN KLAS II A PEKANBARU) - Rosyi Harwinda; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
A person who has been convicted as an imprisonment is placed in prisons or now referred as Correctional Institution. The purpose of this Institution is not simply curbing the right of the independence of inmates, but more than that, the Correctional Institution aims to bring the inmates back to the community as an integrated people and can be responsible for themselves. But the reality does not show the purpose of this Institution as it is only limited to the expectations of the making of law. It is proven from several cases that illustrate the reality of this institution is contrary to legal purpose set up. One of many cases was inmates escaped.The purposes of this research are; First, to know the role of the Correctional Instituion Class II A Pekanbaru in maintaining security in order to prevent the occurrence of inmates escaped. Secondly, to find out the triggers of the inmates escaped in Correctional Instituio Class II A Pekanbaru. The type of this research is sociological legal which author conducts field research in order to deliver a complete and clear picture of the study case. Data collection technique in this research by doing interview, questionnaires, and the literature research.The result of this research can be inferred; First, the role of the Correctional Institution Class II A Pekanbaru in maintaining in security in order to prevent the occurrence on inmates escaped, namely: 1. Preventive Action: The Social Reintegration, of the construction, strengthening the security system. 2. The Repressive Action: Find out the cause of the inmates escaped, chronologically to from special teams to go after inmates, to coordinate with police officer, submit report to the head of the regional Human Right Riau and Director General of Corrections, coordinating with family, friends and inmates circles. Second, the triggers of the inmates escaped in Correctional Instituion Class II A Pekanbaru, namely; 1. The Internal factors; depressed circumstances in Correctional Institution, the chance to escape, a lack of security officer, the number of the occurance of the escape the triggers others inmates desire to follow friends experience in escape, 2. External Factors; finance factors from family, problems with partner which result in divorce. Family, friends and social circumstances which substantiate to escape. Author’s suggestion in this study case; First, applying strict sanctions escaped, embody criminal sanctions and disciplinary action. Secondly, to improve the management performance of Correctional Institution, by improving quality and quantity of the officer like the mentality of Correctional Institution Officer, recruiting the number of Correctional Institution Officer legally and improving the quality of security in Correctional Institution.Keywords: Role-The Correctional Institution-The Inmates Escaped